1988
DOI: 10.1007/bf00445915
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coeliac disease in diabetic children and adolescents

Abstract: Screening for coeliac disease (CD) with serum antigliadin antibodies (AGA) was performed in 1032 diabetic children and adolescents. In 8 children CD had been diagnosed before study entry. Of the remaining 1024 children, 33 had an elevated AGA titre in the first serum sample. On follow-up an elevated AGA titre was confirmed in only 17 of 31 patients. Nine of the repeatedly positive patients underwent jejunal biopsy, and CD was diagnosed in two asymptomatic patients; both were positive for IgG- and IgA-AGA. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
2
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 30 publications
5
58
2
3
Order By: Relevance
“…ith the advent of sensitive and specific serological testing, it is clear that celiac disease is more common than previously thought (1)(2)(3). In children with type 1 diabetes, prevalence rates are in the region of 1-10% compared with 0.01-0.03% in the general population (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…ith the advent of sensitive and specific serological testing, it is clear that celiac disease is more common than previously thought (1)(2)(3). In children with type 1 diabetes, prevalence rates are in the region of 1-10% compared with 0.01-0.03% in the general population (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…All patients reported either partial or complete resolution of their complaints (including musculoskeletal symptoms) upon initiation of the GFD. Ten of the 36 newly diagnosed patients (patients 14,19,20,21,24,26,28,31,34, and 36) never needed any medications and reported complete resolution of their symptoms with the restriction of gluten.…”
Section: Resultsmentioning
confidence: 99%
“…1 In children ages 2.5 to 15 years this prevalence has been reported as between 0.3% and 1.3%. [2][3][4] Studies have shown an association between CD and numerous autoimmune and rheumatic conditions including rheumatoid arthritis, 5,6 juvenile idiopathic arthritis (JIA), [7][8][9][10] autoimmune thyroiditis, [10][11][12] autoimmune thrombocytopenic purpura, hemolytic anemia, 6 vasculitis, 5,6 polymyositis and dermatomyositis, 13,14 systemic lupus erythematosus (SLE), 5,6,15,16 scleroderma, 5,6 mixed connective tissue disease, 5 diabetes mellitus, [17][18][19][20][21][22] Sjögren syndrome, 6,10,23,24 and dermatitis herpetiformis. 24 Among the connective tissue disorders, only Sjögren syndrome appears to share the HLA DQ2/DQ8 haplotype with CD.…”
Section: What This Study Addsmentioning
confidence: 99%
“…There is strong evidence for the association between Type 1 diabetes and CD. [8][9][10][11][12][13][14][15][16][17][18][19] Up to 8% of patients with Type 1 diabetes have the characteristic features of CD on small intestinal biopsy.…”
Section: Introductionmentioning
confidence: 99%